Alimentary Treatment with Trehalose in a Pharmacological Model of Alzheimer's Disease in Mice: Effects of Different Dosages and Treatment Regimens - Alexander B. Pupyshev; Anna A. Akopyan; Michael V. Tenditnik; Marina V. Ovsyukova; Nina I. Dubrovina; Victor M. Belichenko; Tatiana A. Korolenko; Svetlana A. Zozulya; Tatiana P. Klyushnik; Maria A. Tikhonova (MDPI AG, 2024)
In the treatment of experimental neurodegeneration with disaccharide trehalose, various regimens are used, predominantly a 2% solution, drunk for several weeks. We studied the effects of different regimens of dietary trehalose treatment in an amyloid-β (Aβ) 25-35-induced murine model of Alzheimer's disease (AD). Aβ-treated mice received 2% trehalose solution daily, 4% trehalose solution daily (continuous mode) or every other day (intermittent mode), to drink for two weeks. We revealed the dose-dependent effects on autophagy activation in the frontal cortex and hippocampus, and the restoration of behavioral disturbances. A continuous intake of 4% trehalose solution caused the greatest activation of autophagy and the complete recovery of step-through latency in the passive avoidance test that corresponds to associative long-term memory and learning. This regimen also produced an anxiolytic effect in the open field. The effects of all the regimens studied were similar in Aβ load, neuroinflammatory response, and neuronal density in the frontal cortex and hippocampus. Trehalose successfully restored these parameters to the levels of the control group. Thus, high doses of trehalose had increased efficacy towards cognitive impairment in a model of early AD-like pathology. These findings could be taken into account for translational studies and the development of clinical approaches for AD therapy using trehalose.